Software connector as software process. (25th April 2022) - Menasria, Ahcene; Oussalah, Mourad; Amirat, Abdelkrim; Bahi, Halima
In component-based architectures, interest has often been focused on the component. Recent applications are becoming more and more communicative, often reaching equivalent proportions between the interactional and functional parts. This study is interested in explicit connectors by proposing a rich semantic connector to model and implement complex communications in heterogeneous environments. We present a new structure of the connector and model its behaviour through a software process. We no longer consider it as a software product or artefact but rather as a communication process. The connector is treated as a first-class entity with the same degree of citizenship as a component. This research concentrated on the motivations and benefits of first-class connectors and some connector-centric works to arrive at the proposed solution through a Meta-model illustrated by a case study using SPEM profile.